Remdesivir use in the coronavirus disease 2019 Pandemic: A mini-review (2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative viral pathogen of coronavirus disease 2019 (COVID-19), appears to have various clinical presentations and may result in severe respiratory failure. The global SARS-CoV-2-associated viral pneumonia pandemic was first reported in December 2019 in China. Based on known pharmacological mechanisms, many therapeutic drugs have been repurposed to target SARS-CoV-2. Among these drugs, remdesivir appears to be the currently most promising according to several clinical trials and reports of compassionate use. In this mini-review, we summarize the current evidence on the efficacy and challenges of remdesivir for the treatment of coronavirus disease 2019 (COVID-19).